An ecological momentary assessment study assessing repetitive negative thinking as a predictor for psychopathology - Julia Funk; Celina Müller; Tabea Rosenkranz; Benjamin Aas; Cristina Botella; Felix Burkhardt; Johnny R.J. Fontaine; Mads Frost; Azucena Garcia-Palacios; Christiane Hoessle; Veerle E.I. Huyghe; Johanna Löchner; et al. (PLoS ONE, 2025)
Repetitive negative thinking (RNT), an important transdiagnostic process, is commonly assessed using trait questionnaires. While these instruments ask respondents to estimate their general tendency towards RNT, ecological momentary assessment (EMA) allows to assess how much individuals actually engage in RNT in their daily lives. In a sample of N =  1,176 adolescents and young adults, we investigated whether average levels of RNT assessed via EMA predicted psychopathological symptoms. Adjusting for trait RNT measures and baseline scores on outcome measures, we found that average levels of RNT assessed via EMA significantly predicted higher depressive and anxiety symptoms as well as lower mental well-being at baseline, one-, three-, and twelve-month follow-up. Exploratory analyses of the association between temporal dynamics of RNT (e.g., RNT inertia) and psychopathological symptoms yielded inconsistent results. The high predictive power of average scores on the EMA-based RNT measure suggests that EMA is a promising tool for assessing RNT.